The perception of patients regarding comprehensive care rendered by Clinical Nurse Practitioners in the West Coast rural district in the Western Cape - Van Heerden, Petro (Stellenbosch : Stellenbosch University, 2012)
Thesis (MCur)--Stellenbosch University, 2012.